Framing Analysis of Earthquake News on CNN Indonesia Online Media - Shahnaz Sabahunnur Kautsar; Wahyunengsih (UIR Press, 2023)
This research aims to provide information related to news framing analysis on CNN Indonesia online media in the Bali earthquake. This framing analysis research uses the approach by Zhongdang Pan and Gerald M. Kosicki. The method used is descriptive qualitative. The results of this study are based on the use of four structures including 1) The syntactic structure in this news has a headline, 2) the script structure in this news shows that the main purpose of this news is to provide information about the natural earthquake disaster that occurred in Bali, 3) The theme emphasized in this news is about the M 4.8, 4) There are three rhetorical structures in the news, which are shearing, landslides, rock falls. It can be concluded that the syntactic aspect in the headline section is mentioning the Earthquake in Bali. The lead and background information contains information from BMKG. For the quotation section, there is only one source, namely Daryono. Then, CNN Indonesia online media does not write statements and opinions in the news. The script element in this media has reached perfection, where CNN has used the 5W + 1H elements in writing its news properly and correctly. The thematic element in CNN Indonesia media is explanatory coherence. Lastly, the rhetorical element in the media uses a choice of substitute words that are rarely known by the public